THE EXHAUSTION OF COOLING-OFF PERIOD: A NON-MANDATORY PRE-CONDITION IN INVESTMENT ARBITRATION - Belaputri, Addyana; Joshua, Gregory; Febria, Jesslyn; Marwandy, Muhammad Irsyad (Transnational Business Law Journal, 2021)
Arbitration as an alternative institution to settle commercial disputes has been widely recognized by the business community and state governments. Dispute settlement through arbitration usually derives from the treaty or contract breach which is put under dispute settlement clause. In regard to investor-state dispute settlement, international arbitration plays an important role. However, there are several admissibility requirements that relate to the jurisdiction of the Tribunal, in particular, cooling-off period requirement. This article is placed for the nature and provision of cooling-off period requirement by analyzing several precedent jurisprudences through juridical normative methods. The cooling-off period in Investment Arbitration has been considered as jurisdictional requirement which also integrated with the procedural requirement to submit investment dispute to ISDS arbitration.